Exploring the realm of bacteria: a practical approach during the Supervised Internship in Biological Sciences (Research, Society and Development, 2023)
This article presents a series of classes taught by a research intern during her Supervised Internship of the Biological Sciences Course, addressing the topic of bacteria. The methodological approach of these writings approaches post-critical postures in education and configures an experience report. In the process of building the classes, several didactic resources were employed, such as concept maps and ludic activities, following the methodology of the Three Pedagogical Moments, in order to provide an alternative approach to scientific teaching throughout the classes. In addition, reflections and concerns arising during the teaching practice were recorded in written diaries, known as Pedagogical Practice Journal, serving as a tool for reflecting on and researching the actions taken and involving multiple authors in the process to compose and analyze teaching and its intersections. A remarkable engagement and enthusiasm from the students were observed in the differentiated classes, as well a certain discomfort with scientific terminology, highlighting the importance of science education connected to the students' reality, as well as paying attention to the particularities and individualities of the individuals present in the school environment.